Pengaruh Lama dan Suhu Penyimpanan Ekstrak Daun Sirih Hijau (Piper betle linn) Dengan Aquades Terhadap Daya Hambat Bakteri Streptococcus agalactiae Penyebab Mastitis pada Sapi Perah - Muhammad Sanjaya Kusuma; Tri Eko Susilorini; Puguh Surjowardojo (TERNAK TROPIKA Journal of Tropical Animal Production, 2017)
Green betle leaf (Piper betle L.) is one of the plants used by the people of Indonesia for tradisional medicine. Green betle leaf contains antibacterial compounds consisting of phenol and its derivatives. This study aims to determine the antibacterial activity of green betle leaf (Piper betle L.) againt the bacteria Streptococcus agalactiae caused mastitis in dairy cows. Bacterial inhibition test by paper disc method. Data analysis using ANOVA by Nested design with 6 treatment and 6 repetitions. The results of this study green betle leaf (Piper betle L.) extract inhibiting the growth of bacteria Streptococcus agalactiae was significantly different (P<0,01). The conclusion were the extract of green betel leaf (Piper betle L.) can inhibit the growth of Streptococcus agalactiae and storage temperature has no effect, but storage periode gives effect the quality of green betel leaf extract (Piper betle L.), so that the leaf extract storage green betel with distilled solvent recommended on 2nd days at refrigerator.